Sample Size Estimation and Statistical Analysis of Cholangiography Robots - Tang, Rongli (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In recent years, with the continuous innovation of medical devices encouraged by the government and the investment and attention of enterprises in research and development, coupled with the relevant requirements of the CDE (Center for Drug Evaluation) of the National Medical Products Administration, in order to improve the efficiency of trials and accelerate the launch of cholangiography robots, medical device research and development enterprises are increasingly focusing on the design of clinical trial plans, adopting more scientific, reliable, efficient and standardized statistical designs. Insufficient sample size may lead to issues with sample representativeness, while human centered trials are very expensive, and excessive sample size could increase the difficulty of clinical research. Therefore, this study used the "golden rule" of RCT (Randomized Controlled Trials), combined with the outcome indicators, test level, confidence, dropout rate, etc., to estimate the number of cases in the clinical efficacy comparison study of the cholangiography robot.